Parecoxib nel trattamento del dolore post-operatorio: considerazioni farmacoeconomiche - Mathis, Federica; Pradelli, Lorenzo; Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2004)
Parecoxib sodium is the first selective COX- 2 inhibitor to be available for parenteral administration. This pharmaceutical feature, alongside its favorable efficacy and safety profile, makes the new drug particularly suitable for simple and effective management of post-surgical pain. Aim of this work is to describe the pharmacoeconomical profile of the drug in the Italian setting, focusing on the comparison with parenteral ketorolac, the most widely prescribed treatment for post-surgical pain in Italy. The first part of the article describes the most important pharmacological characteristics of parecoxib and reviews the main efficacy and safety studies that were performed on patients presenting with post-surgical pain. A similar article about parecoxib was published on “Farmeconomia e percorsi terapeutici” 2003; 4(1): 39-50. At that moment, the price to the public wasn’t yet fixed and therefore the pharmacoeconomical analysis was based on estimated price. Moreover, during this year, extra studies were published on the efficacy of parecoxib on patients with post-surgical pain. For these reasons, we intend to present here an updated version of the profile.